Evaluation of pear lmillet (Pennisetum glaucum) and mothbean (Vigna acconitifolia) intercropping systems in hyper arid partially irrigated north-western plains zone - KURI, B R; YADAV, R S; KUMAWAT, AMIT (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during kharif 2008 to evaluate different row ratio of pearl millet + mothbean in the arid region of Rajasthan. The treatments comprised three sole pearl millet at 30, 40 and 60 cm spacing, one sole mothbean and eleven pearl millet + mothbean treatments [1:3, 1:7, 2:2, 2:6, 3:1, 3:5, 4:4, 5:3, 6:2, 7:1 and 2:1 (check) row ratio]. The intercropping of pearl millet + mothbean in 1:7 row ratio closely followed by 4:4, 2:6 and 3:5 row ratio, produced maximum pearl millet equivalent yield (PMEY), LER and net returns and also better nutrient uptake by these treatments compared to sole and other intercropping treatments. Aggressivity values showed that intercrop mothbean did not offer any competition to pearl millet in different row ratio, while RCC values indicated that there was a yield disadvantage in mothbean in all the intercropping system except 1:7 row ratio. Competition ratio indicated that row ratios such as 3:1 and 2:1 which offer less space to mothbean (intercrop) that leads to lower yield of intercrop as component crop (pearl millet) offer greater competition for mothbean in these row ratios.